Mempelajari Reaksi Transesterifikasi Terkatalisis Kalsium Oksida - nia yuniar kandou; Sanusi Gugule; Anderson Arnold Aloanis (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Research on the virgin coconut oil transesterification reaction catalyzed calcium oxide has been carried and determination of its characteristics include physico-chemical properties, analysis of reactions results using infrared spectrophotometry and gas chromatography-mass spectrometry (GCMS). The purpose of this research is to study the transesterification reaction catalyzed calcium oxide and find out its characteristics. VCO transesterification reaction catalyzed calcium oxide was carried out for 3 hours at a temperature 7 with a catalyst of 1%. The results of this reaction have as much yield ; 39,89% and the alleged characteristic change due to new ester that is, density 0,88 g/mL, kinematic viscosity 2,73 mm2/s (cSt), acid number 0,59 mg KOH/g, ester number 148,43 mg KOH/g and peroxide number 4,27 mek O2/kg. The results of infrared spectrophotometry analysis showed absorption bands for ester and GCMS analysis gave the peak of the compound suspected as ethyl ester with three peaks which had the most abundance in the form of ethyl laurate 58,32%, ethyl myristate 16,82% and ethyl palmitate 6,92%.